National trends in coronary intensive care unit admissions, resource utilization, and outcomes. Issue 8 (December 2020) - Woolridge, Sarah; Alemayehu, Wendimagegn; Kaul, Padma; Fordyce, Christopher B; Lawler, Patrick R; Lemay, Michel; Jentzer, Jacob C; Goldfarb, Michael; Wong, Graham C; Armstrong, Paul W; van Diepen, Sean
Background: Emerging evidence suggests that coronary intensive care units are evolving into intensive care environments with an increasing burden of non-cardiovascular illness, but previous studies have been limited to older populations or single center experiences. Methods: Canadian national health-care data was used to identify all patients ≥18 years admitted to dedicated coronary intensive care units (2005–2015) and admissions were categorized as primary cardiac or non-cardiac. The outcomes of interest included longitudinal trends in admission diagnoses, critical care therapies, and all-cause in-hospital mortality. Results: Among the 373, 992 patients admitted to a coronary intensive care unit, minimal changes in the proportion of patients admitted with a primary cardiac (88.2% to 86.9%; p <0.001) and non-cardiac diagnoses (11.8% to 13.1%; p <0.001) were observed. Among cardiac admissions, a temporal increase in the proportion of ST-segment elevation myocardial infarction (19.4% to 24.1%, p <0.001), non-ST-segment elevation myocardial infarction (14.6% to 16.2%, p <0.001), heart failure (7.3% to 8.4%, p <0.001), shock (4.9% to 5.7%, p <0.001), and decline in unstable angina (4.9% to 4.0%, p <0.001) and stable coronary diseases (21.3% to 12.4%, p <0.001) was observed. The proportion of patients requiring critical care therapies (57.8% to 63.5%, p <0.001) including mechanical ventilation (9.6% to 13.1%, p <0.001) increased. In-hospital mortality rates for patients with primary cardiac (4.9% to 4.4%; adjusted odds ratio 0.71, 95% confidence interval 0.63–0.79) and non-cardiac (17.8% to 16.1%; adjusted odds ratio 0.84, 0.73–0.97) declined; results were consistent when stratified by academic vs community hospital, and by the presence of on-site percutaneous coronary intervention. Conclusion: In a national dataset we observed a changing case-mix among patients admitted to a coronary intensive care unit, though the proportion of patients with a primary cardiac diagnosis remained stable. There was an increase in clinical acuity highlighted by critical care therapies, but in-hospital mortality rates for both primary cardiac and non-cardiac conditions declined across all hospitals. Our findings confirm the changing coronary intensive care unit case-mix and have implications for future coronary intensive care unit training and staffing.